Handbook of research on intrusion detection systems - Gupta, Brij 1982; Srinivasagopalan, Srivathsan 1974 (A volume in the advaces in information security, privacy, and ethics (AISPE) book series, 2020)
"This book explores recent developments and applications in intrusion detection systems and intrusion detection security"--